Carnauba leaf fibers: correlation among diametrical variation, physical and mechanical properties - Raí Felipe Pereira Junio; Lucas de Mendonça Neuba; Artur Camposo Pereira; Andressa Teixeira Souza; Lara Maria Macêdo Isidoro; Lúcio Fabio Cassiano Nascimento; Sergio Neves Monteiro (Journal of Materials Research and Technology, 2023)
The variability of properties presented by natural lignocellulosic fibers (NLFs) is an important issue to highlight, since such inconsistencies in their characteristics put them at a disadvantage when comparing them to synthetic materials. It is important to point out that the application of methodologies that make it possible to predict the behavior of NLFs in the face of mechanical stress is essential for the use of these materials in engineering applications. For this, the present study proposes to evaluate the influence of the carnauba fibers (Copernicia prunifera) morphology in the properties presented by these materials. Optical microscopy (OM) was applied to determine the cross-section and diametrical variation of the fibers, enabling the evaluation of density by Archimedes method according to the mean diameter of the fibers. The mechanical properties were evaluated by tensile testing and the data were acquired by Weibull analysis. The morphological aspects of the longitudinal and cross-sections of the fibers were evaluated with scanning electron microscopy (SEM). The fibers had an average density of 1.13 ± 0.22 g/cm3, with diameter intervals ranging from 0.31 to 1.21 mm. The fibers have reasonable mechanical properties, with an average tensile strength of 64.7 ± 40.9 MPa, Young's modulus of 1.37 ± 0.80 GPa and elongation of 5.59 ± 1.60%. The SEM micrographs highlighted the defects present on the outer surface of the fiber as well as in the cross-section. There was a high potential for the use of carnauba fibers in the manufacture of polymer matrix composites.